Corporate Social Responsibility Market Reaction and Accounting Conservatism with Investor Protection and Stock Liquidity - Hu Zhangze, Van; Wang Y. L, Li (Advances in Accounting Innovation, 2025)
Purpose – This study investigates the links between CSR, market response and accounting conservatism, focusing on the moderating influences of investor protection and stock liquidity. We hypothesise that active involvement in CSR initiatives tends to improve accounting conservatism and that this relationship is moderated by external governance mechanisms.Design/methodology/approach – This study uses multi-year panel data of listed companies and applies a two-stage least squares (2SLS) regression model. To ensure robustness, several CSR proxies are examined. These include environmental, social and governance (ESG) dimensions. To address endogeneity concerns, the study controls for both firm characteristics, industry-specific effects and aggregator macro conditions.Findings – The results show that CSR affects accounting conservatism positively, especially when in firms with effective investor protection and high stock liquidity. Companies with higher CSR engagement show less earnings management, a sign of increased accounting quality and governance. These results are stable across robustness checks as to alternative conservatism proxies and CSR components.Originality/value – While previous studies considered CSR and conservatism separately, this study takes investor protection and stock liquidity as moderator variables, thus showing a comprehensive view of the governance role of CSR. Moreover, it uses various CSR proxies and alternative conservatism measures, providing a much more detailed and reliable analysis.Research Implications – The research emphasises that CSR goes beyond social objectives. As a strategic tool, it is a means for companies to increase financial transparency and investor confidence. Policy makers should explore ways to further strengthen investor protection regimes to reap the governance benefits of CSR. And investors and regulators can use CSR disclosures to assess companies' financial prudence and risk management practices, thereby promoting more stable and trusted financial markets.